2020
DOI: 10.1002/slct.202003744
|View full text |Cite
|
Sign up to set email alerts
|

De‐fluoridation of Polluted Water Using Aluminium Alginate Beads Doped with Green Synthesized ‘Nano SiO2+Nano CeO2‐ZrO2’, as an Effective Adsorbent

Abstract: Nanoparticles of SiO2 and ‘CeO2‐ZrO2’ are synthesized by adopting new green methods based on the classical method of homogeneous precipitation and using the extract of skins of Sapindus plant seeds as capping and/or stabilizing agent. Nano SiO2 is synthesized from red mud, a waste material obtained after extraction of aluminium from Bauxite ore. Nano SiO2, composites of ‘nSiO2+nCeO2‐ZrO2’ and Al‐alginate beads doped with ‘nSiO2+nCeO2‐ZrO2’ are investigated as adsorbents for de‐fluoridation. These three adsorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This inferred the phosphate adsorption process onto Cc-ZnO and Ra-ZnO may be mainly controlled by chemisorption and the adsorptive behavior might incorporate the valency forces through sharing electrons between phosphate ions and composite. [25][26][27] The kinetic models mentioned above could not explain the diffusion mechanism well, then the intra-particle diffusion model (3) was used to further explain the role of diffusion in the phosphate adsorption.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…This inferred the phosphate adsorption process onto Cc-ZnO and Ra-ZnO may be mainly controlled by chemisorption and the adsorptive behavior might incorporate the valency forces through sharing electrons between phosphate ions and composite. [25][26][27] The kinetic models mentioned above could not explain the diffusion mechanism well, then the intra-particle diffusion model (3) was used to further explain the role of diffusion in the phosphate adsorption.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…The literature search revealed that several reports have described the green synthesis of alumina nanocomposites as potential sorbents for water treatment. These reports include green synthesis of iron–aluminum nanocomposites, aluminum alginate beads doped with metal oxides, a 3D hydrogel based on alumina and GO cellulose, and bionanocomposites based on fungal hyphae for fluoride removal from water. …”
Section: Introductionmentioning
confidence: 99%